Significance of Kynurenine 3-Monooxygenase Expression in Colorectal Cancer - Liu, Chun-Yu; Huang, Tzu-Ting; Chen, Ji-Lin; Chu, Pei-Yi; Lee, Chia-Han; Lee, Hsin-Chen; Lee, Yu-Hsuan; Chang, Yuan-Ya; Yang, Shung-Haur; Jiang, Jeng-Kai; Chen, Wei-Shone; Chao, Yee; et al. (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is a leading cause of cancer-related deaths. Because of the lack of reliable prognostic and predictive biomarkers for CRC, most patients are often diagnosed at a late stage. The tryptophan-kynurenine pathway plays a crucial role in promoting cancer progression. Kynurenine is considered an oncometabolite in colon cancer, and its downstream metabolites are also associated with CRC. Kynurenine 3-monooxygenase (KMO), a pivotal enzyme that catalyzes kynurenine metabolism, is essential for several cellular processes. In the current study, we explored the role of KMO in CRC. Immunohistochemical results showed that KMO was upregulated in CRC tissues relative to paired healthy tissue and polyps. Moreover, CRC patients with higher KMO expression were associated with higher metastasis and poorer survival rates. Knockdown of KMO decreased the expression of cancer stem cell markers, as well as the sphere-forming, migration, and invasion abilities of CRC cells. Additionally, blockade of the enzymatic activity of KMO using an inhibitor suppressed sphere formation and cell motility in CRC cells. These findings suggest the clinical relevance of KMO in CRC tumorigenesis and aggressiveness.